Modal shift behavior towards bus rapid transit in Indonesia: A systematic literature review - Nadira Nurul Diniyah (Journal of Placemaking and Streetscape Design, 2026)
Background: Commuting is a prevalent activity for Indonesian people. People commute for various activities, but most of them choose to use their private vehicles in their daily mobility, inferring that the willingness to choose public transportation is still low. The huge reliance on private vehicles has various impacts, such as creating heavier traffic congestion and worsening the air pollution. Hence, modal shift behavior of the passengers from private vehicles to public transport is essential. This study aims to analyze the research trends and development of modal shift behavior towards Bus Rapid Transit (BRT) systems in Indonesia and synthesize the main influencing factors. Methods: This quantitatively synthesized study applies a systematic literature review where the articles published in relevant academic databases from 2004 to 2026 were collected and went through identification, screening, eligibility, and inclusion based on the PRISMA framework. The 251 selected articles were analyzed and reveal that BRT has been able to support the commuters to shift towards public transportation. Findings: The bibliometric analysis using Bibliometrix and VOSViewer software and further systematic content analysis were employed. Some studies also used the theory of planned behavior (TPB) as their approach. Several key factors influencing the modal shift behavior of the passengers are time travel, accessibility, service quality, and cost efficiency. Therefore, BRT has significant potential to increase the use of public transportation in Indonesia and the modal shift behavior of the commuters. Conclusion: Future study is recommended to explore the modal shift behavior towards other types of public transportation and analyze the environmental impacts of public transportation in Indonesia. Novelty/Originality of this article: This review contributes in providing a comprehensive synthesis of the relevant research in supporting the policy makers in designing strategies to optimize the use of BRT as well as in developing better sustainable transportation in urban cities across Indonesia.